A Review on the Pedal Error Cases Among Car Drivers in Malaysia - Nursya Mimie Ayuny, Ismail; Mohamad Zairi, Baharom; Zulkifli, Ahmad@Manap; Mohd Hasnun Ariff, Hassan; Juffrizal, Karjanto; Zulhaidi, Mohd Jawi; Khairil Anwar, Abu Kassim (Springer, Singapore, 2024)
Human error has caused about 90% of car accidents. The problem of sudden acceleration while driving is the main focus of this analysis. Every year, it has caused people injuries and deaths on Malaysian roads. This paper aims to observe the mistakes in pedal use reported in Malaysian news. The aim is to an-alyze why these mistakes happen and what causes them. Words like “tertekan pedal”, “pedal minyak”, pedal error, pedal misapplication, and sudden unin-tended acceleration are used to find related news articles.